The Impact of Supervisor Gender on Employee Creativity and the Mediating Role of Interaction Frequency - Chadwick, Holly; Yavuz, Isil; Jiang, Crystal; Rustambekov, Elzotbek (Journal of Comparative International Management, 2024)
While it is well established that leader characteristics influence employee outcomes, little is known about whether and how leader gender influences employee creativity. Traditionally, female leaders are considered a mismatch for prototypical leadership roles, resulting in less optimal employee outcomes than male leaders. In this paper, drawing on social role and leader-member exchange theories, we argue that female supervisors may have advantages over male supervisors and may serve as a catalyst to encourage employee creativity. In the empirical analyses, we test our hypotheses using data from German, Japanese, and South Korean foreignsubsidiaries in China. Results confirm our hypotheses and contribute to creativity and innovation literature by demonstrating that female supervisors positively influence employee creativity, challenging traditional gender role stereotypes in leadership. Additionally, it highlights the mediating role of supervisor-employee interaction frequency in enhancing creative outcomes, providing important insights for organizational practices and leadership development.